Le cabaret du chat noir à Montmartre (1881-1897) - Oberthür, Mariel 1945- (Genève Slatkine, 2007)
A meeting place for literary and artistic bohemians as well as the Parisian elite, the Chat Noir cabaret at the foot of Montmartre hill, created and run by Rodolphe Salis, was for more than fifteen years, from 1881 to 1897, a place of creation, entertainment and spectacle that was unique at the time and has become legendary today. Poems and songs performed every evening under the guidance of its genial pitchman made the Chat Noir a veritable popular music hall, with a repertoire quite different from that of the café concert. This book tells the story of this cabaret and its weekly newspaper, which published poems, columns and texts by some of the greatest names in literature, as well as cartoons and topical drawings by illustrators such as Steinlen, Willette and Caran d'Ache, forerunners of today's comic strips. Last but not least, it was at the Chat Noir that Henri Rivière directed and took shadow theatre to its apogee with over forty shows, spreading throughout Europe and heralding the arrival of the cinematograph, which did not yet exist. (Translated with DeepL.com)
Includes bibliographical references (p. [263]-269) and index.
Keywords: Chat noir (Paris, France); 19th Century (1801-1900); Cultural history; Theater history; Cabaret; Literature; Illustration; Satire; Paris (France)